2020
DOI: 10.1364/boe.386999
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating different grades of cervical intraepithelial neoplasia based on label-free phasor fluorescence lifetime imaging microscopy

Abstract: This study proposed label-free fluorescence lifetime imaging and phasor analysis methods to discriminate different grades of cervical intraepithelial neoplasia (CIN). The human cervical tissue lesions associated with cellular metabolic abnormalities were detected by the status changes of important coenzymes in cells and tissues, reduced nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) and flavin adenine dinucleotide (FAD). Fluorescence lifetime imaging microscopy (FLIM) was used to study human cervical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…Reproduced with permission from Ref. [ 56 ]. Copyright 2020, Optical Society of America; a-iii NADH/NAD + ratio is applied for ascertaining tumor fronts.…”
Section: Flim Combined With Nad(p)h For Cancer Metabolism Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission from Ref. [ 56 ]. Copyright 2020, Optical Society of America; a-iii NADH/NAD + ratio is applied for ascertaining tumor fronts.…”
Section: Flim Combined With Nad(p)h For Cancer Metabolism Monitoringmentioning
confidence: 99%
“…Furthermore, for clinical diagnosis, Phasor-FLIM has been successfully applied to cervical intraepithelial neoplasia (CIN) and neoplastic skin lesions, as shown in the phasor plot in Fig. 3a-ii [ 56 ]. This method is also adopted to glioblastoma multiforms (GBMs), leukemia subpopulation classification (Fig.…”
Section: Flim Combined With Nad(p)h For Cancer Metabolism Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Family with sequence similarity 73, member A (FAM73A) is the downregulated gene of DNA from exfoliated cervical cells in terms of the HPV-16 variant analysis (Green, 2019;Meng et al, 2020). CRYZL1 contains a reduced nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) binding site which is involved in cellular metabolism, while cervical lesions are associated with cellular metabolic abnormalities (Wang et al, 2020). It is previously found that the members of the ZNF family interact with nucleic acids, proteins, and small molecules and are involved in a variety of crucial molecular processes in cervical tumor cells at replication, transcriptional, and translational levels.…”
Section: Acat Combining P-values From Different Prediction Modelsmentioning
confidence: 99%
“…Cervical cancer is one of the most common malignant tumors. Early diagnosis and early treatment are important for patients' prognoses [1][2][3]. Cervical cancer can be prevented through Human Papillomavirus (HPV) vaccine injection (primary prevention) and HPV DNA detection cervical exfoliated cell cytological screening (secondary prevention).…”
Section: Introductionmentioning
confidence: 99%